- #1
Matt Jacques
- 81
- 0
Since my other thread is lacking attention, perhaps it is more suitable here:
I inserted some fixed constants and multiplied out
(48/.5)(1-^e-.5t)(sin 45) + (9.8/.25)(1-(.5t) - e^-.5t) = 0
(96 - 96e^-.5t)(sin 45) + 39.2(1-(.5t)-e^-.5t) = 0
67.88 - 67.88^e-.5t + 39.2 - 19.6t - 19.6e^-.5 = 0
107.2 - 87.48e^-.5t - 19.6t = 0
107.2 - 19.6t = 87.48^e-.5t
log(107.2 - 19.6t) = log(87.48^e-.5t)
log107.2 - log19.6t = -.5tLog(87.48)
2.030194 - log19.6t = -.5t(1.94198)
1.045463 - log19.6t = -.5t
-(1.045463 - log19.6t = -.5t)
-1.045463 + log19.6t = .5t
log19.6t = .5t + 1.045463
10^(.5t + 1.045463) = 19.6t
This is where I am stuck.
I inserted some fixed constants and multiplied out
(48/.5)(1-^e-.5t)(sin 45) + (9.8/.25)(1-(.5t) - e^-.5t) = 0
(96 - 96e^-.5t)(sin 45) + 39.2(1-(.5t)-e^-.5t) = 0
67.88 - 67.88^e-.5t + 39.2 - 19.6t - 19.6e^-.5 = 0
107.2 - 87.48e^-.5t - 19.6t = 0
107.2 - 19.6t = 87.48^e-.5t
log(107.2 - 19.6t) = log(87.48^e-.5t)
log107.2 - log19.6t = -.5tLog(87.48)
2.030194 - log19.6t = -.5t(1.94198)
1.045463 - log19.6t = -.5t
-(1.045463 - log19.6t = -.5t)
-1.045463 + log19.6t = .5t
log19.6t = .5t + 1.045463
10^(.5t + 1.045463) = 19.6t
This is where I am stuck.